Conflict Calamities: Natural Disasters and the CPP-NPA - Eastin, Joshua (Kasarinlan: Philippine Journal of Third World Studies, 2018)
This study examines the effects of natural disaster inundation on the internal armed conflict waged by the Communist Party of the Philippines–New People’s Army (CPP-NPA) against the Philippine state. Drawing on interviews and ethnographic data and employing insights from the literature on civil conflict, social movements, and environmental security, this study suggests that the Philippines’ vulnerability to disaster has provided the CPP-NPA with tactical opportunities to increase attacks against the Armed Forces of the Philippines (AFP), and has enabled the group to penetrate affected communities to increase civilian collaboration and augment recruitment. In some cases, the Philippine state’s institutional architecture for humanitarian relief, which relies heavily on local government units, has abetted this process by enabling local politicians to distribute relief supplies according to political patronage. The effect marginalizes individuals and groups from the political process and enhances the receptivity of the CPP-NPA’s anti-state propaganda. The overall impact has been to prolong the CPP NPA’s ability to maintain its revolutionary campaign and increase the group’s capacity to wage violence.
Keywords: conflict; natural disasters; CPP-NPA; vulnerability